Do Personality Traits Predict Skepticism? Locus of Control Mediation in Public Audits - Victor Pattiasina; Khusnul Khotimah; Nur Choirul Afif; Amena Sibghatulla (Universitas Negeri Malang, 2026)
This study examines the mediating role of locus of control in the relationship between openness, conscientiousness, and professional skepticism among public sector auditors at the Audit Board of the Republic of Indonesia (BPK RI) Representative Office of Papua Province. Using a quantitative explanatory design, data were collected through a survey questionnaire distributed to all 150 auditors using a saturated sampling approach, with 132 valid responses analyzed. The study employed SmartPLS 4 to test the measurement and structural models. The results indicate that openness and conscientiousness have positive and significant effects on professional skepticism. Both personality traits also positively influence locus of control, which in turn significantly affects professional skepticism. Furthermore, locus of control partially mediates the effects of openness and conscientiousness on professional skepticism. These findings suggest that auditors with stronger openness, conscientiousness, and internal locus of control tend to demonstrate a higher level of professional skepticism in conducting audits. The study contributes to the auditing literature by extending Social Cognitive Theory in explaining the psychological mechanism underlying skeptical judgment in the public sector audit context. Practically, the findings imply that audit institutions should strengthen auditors’ psychological development through training, supervision, and recruitment policies that support adaptive personality traits and internal control orientation to improve audit quality and public accountability.